2021
DOI: 10.1017/s0033291720004547
|View full text |Cite
|
Sign up to set email alerts
|

The role of lifetime stressors in adult fibromyalgia: systematic review and meta-analysis of case-control studies

Abstract: BackgroundFibromyalgia is a chronic condition characterised by widespread musculoskeletal pain. Although accumulating evidence suggests that exposure to stressful events increases the risk for this complex disorder, this is the first meta-analysis to compare the impact of a full range of lifetime stressors (e.g. physical trauma through to emotional neglect) on adult fibromyalgia.MethodsThis review was performed in accordance with PRISMA guidelines. Random-effects models examined associations between different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…A history of childhood abuse and neglect substantially contributes to physical disease in adulthood, although this has been more widely studied in the context of mental illnesses (41). A meta-analysis of 19 studies by Kaleycheva et al (42) has confirmed significant associations between adult FM and exposure to stressors such as physical abuse, total abuse, sexual abuse, medical trauma, other lifetime stressors, and emotional abuse.…”
Section: Life Traumasmentioning
confidence: 92%
“…A history of childhood abuse and neglect substantially contributes to physical disease in adulthood, although this has been more widely studied in the context of mental illnesses (41). A meta-analysis of 19 studies by Kaleycheva et al (42) has confirmed significant associations between adult FM and exposure to stressors such as physical abuse, total abuse, sexual abuse, medical trauma, other lifetime stressors, and emotional abuse.…”
Section: Life Traumasmentioning
confidence: 92%
“…However, while specific gene candidates associated with FM have indeed been identified 18 and include potentially important DNA patterns (e.g., hypomethylation), 19 there is simultaneous acknowledgment of strong evidence pointing to environmental factors. For example, recent meta-analytic findings show a significant association between FM and exposure to traumatic stress, 20 and a systematic review reported that psychological trauma frequently appears to immediately precede onset of FM. 21 These potentially distinctive causal pathways may differentially alter brain structure and function, yielding an assortment of clinical presentations that are relatively unalike despite fitting the FM diagnostic criteria for research.…”
Section: Overview Of Fibromyalgia and Variability Inherent In The Cli...mentioning
confidence: 99%
“…(2) comprised by women with FMS; (3) with at least two groups; (4) of which one group received VRBT; (5) compared with controls; (6) and reported quantitative data of different outcomes related with FMS impact (see Section 2.5). The exclusion criteria that were established included (1) experimental studies without a comparison group and (2) studies comprising patients with a variety of musculoskeletal disorders (i.e., not only FMS).…”
Section: Study Selection and Inclusion Criteriamentioning
confidence: 99%
“…Fibromyalgia syndrome (FMS) is a chronic disease of unknown etiology that courses with generalized and diffuse non-inflammatory pain and hyperalgesia in different human body points [1]. Other FMS symptoms are joint stiffness [2], generalized fatigue [3], impaired balance [4], anxiety and depression [5], and emotional overload [6] that reduces functional capacity [7] personal autonomy, social relationships [8] and quality of life (QoL) [9,10]. The global prevalence of FMS ranges between 2% and 8% of the population [11], mainly affects women (61-90%) [12] aged 50 years and over [13] and involve a large consumption of social and health resources [14].…”
Section: Introductionmentioning
confidence: 99%